MATLAB and Simulink resources for Arduino, LEGO, and Raspberry Pi

Learn moreOpportunities for recent engineering grads.

Apply TodayThe Fibonacci sequence is defined as:

Fib(1) = 0 Fib(2) = 1 Fib(N) = Fib(N-1) + Fib(N-2)

The Fibonacci sequence can be generalize as follow:

Fib_gen(1) = a Fib_gen(2) = b Fib_gen(N) = Fib_gen(N-1) + Fib_gen(N-2)

where 0 >= a >= b

Moreover it can be shown that

Fib_gen(N) = k(1) * Fib(N) + k(2) * Fib(N+1)

Given a and b find k(1) and k(2).

22 correct solutions
5 incorrect solutions

Last solution submitted on Nov 21, 2014

2 players like this problem